A second chance: analyzing trends and outcomes for reapplicants in orthopaedic surgery - Major, Edward L.; Shah, Vivek P.; Goetz, James R.; Badarudeen, Sameer (International Journal of Research in Orthopaedics, 2025)
Background: The increasing number of applicants for orthopaedic surgery residency programs, paired with a static number of available positions, has resulted in many candidates being unmatched. This study explored trends and factors associated with successful reapplication outcomes for unmatched orthopaedic surgery applicants. Methods: This mixed-methods study was conducted between June 2024 and January 2025. Inclusion criteria for qualitative data were unmatched orthopaedic surgery applicants who subsequently matched and participated in interviews. Exclusion criteria included those who did not reapply or did not complete the interview process. Data were obtained from the Orthopaedic Residency Information Network (ORIN) and included demographics of current residents, attending faculty, and residency program characteristics. Gender of program leaders was verified through LinkedIn and program websites. Spearman correlation and ANOVA were used for analysis, with significant variables further examined through multiple regression. Qualitative insights were collected through interviews with previously unmatched applicants who matched on subsequent attempts. Results: Analysis revealed no statistically significant associations between traditional metrics (e.g., USMLE scores, demographics) and matching outcomes (p>0.05). Qualitative data highlighted that engagement in research and clinical experiences, as well as meaningful mentorship, significantly impacted reapplication success. Conclusions: Despite the lack of significant predictors from traditional metrics, proactive measures taken during the year off were crucial for unmatched applicants. Candidates should focus on strategic activities to enhance their competitiveness in future applications.